2023
DOI: 10.1038/s41467-023-36692-w
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic nature of netrin-1 and the structural basis for glycosaminoglycan fragment-induced filament formation

Abstract: Netrin-1 is a bifunctional chemotropic guidance cue that plays key roles in diverse cellular processes including axon pathfinding, cell migration, adhesion, differentiation, and survival. Here, we present a molecular understanding of netrin-1 mediated interactions with glycosaminoglycan chains of diverse heparan sulfate proteoglycans (HSPGs) and short heparin oligosaccharides. Whereas interactions with HSPGs act as platform to co-localise netrin-1 close to the cell surface, heparin oligosaccharides have a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 105 publications
1
2
0
Order By: Relevance
“…During the review of our manuscript, two articles were released that complement our findings on the roles of proteoglycans and GAGs in netrin and/or UNC-5 function. Meier et al (57) observed that vertebrate netrins oligomerize with heparin through interactions with their EGF2 domains, similar to our findings with UNC-6, and breaking this interaction in the nematode model results in the distal tip cell migration phenotype as we have shown for UNC-5. Akkermans et al (58) showed that mouse UNC5D can form oligomers with a glypican, but without contacting the HS chain.…”
Section: Discussionsupporting
confidence: 91%
“…During the review of our manuscript, two articles were released that complement our findings on the roles of proteoglycans and GAGs in netrin and/or UNC-5 function. Meier et al (57) observed that vertebrate netrins oligomerize with heparin through interactions with their EGF2 domains, similar to our findings with UNC-6, and breaking this interaction in the nematode model results in the distal tip cell migration phenotype as we have shown for UNC-5. Akkermans et al (58) showed that mouse UNC5D can form oligomers with a glypican, but without contacting the HS chain.…”
Section: Discussionsupporting
confidence: 91%
“…( B ) Fibroblast growth factor 2 (FGF2) in complex with fibroblast growth factor receptor 1 (FGFR1), which is mediated by a long-chain heparin ligand (PDB ID: 1FQ9) [ 25 ]. ( C ) Netrin-1 (Net-1) in complex with sucrose octasulfate (SOS) (PDB ID: 7LRF) [ 32 ]. ( D ) Platelet factor 4 (PF4) in complex with the heparin mimetic fondaparinux (PDB ID: 4R9W) [ 33 ].…”
Section: Figurementioning
confidence: 99%
“…S1) containing the mutant sequence (GeneArt String, Invitrogen) replaced the respective wild-type sequence and was amplified by PCR. Wild type and mutant PCR products were cloned into a modified pCEP-pu vector containing an N-terminal BM40 signal peptide and an N-terminal One-STrEP-tag or an N-terminal His 8 tag [38,39]. The recombinant plasmids were introduced into HEK293-EBNA cells (Invitrogen) using the FuGENE 6 transfection reagent (Roche Applied Science).…”
Section: Introductionmentioning
confidence: 99%